PERLINDUNGAN HUKUM TERHADAP DEBITUR DALAM PROSES PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) SEBAGAI UPAYA PENCEGAHAN KEPAILITAN (Studi Putusan No. 8/Pdt.Sus-PKPU/2025 PN Niaga Medan) - Lambaik Manalu, Bonanda Japatani Siregar (NERACA KEADILAN, 2026)
The Suspension of Debt Payment Obligations (PKPU) is a legal instrument aimed at providing protection to debtors to avoid bankruptcy through debt restructuring with creditors. However, in practice, the effectiveness of legal protection for debtors in the PKPU process still faces various obstacles, both from the legal, economic, and sociological aspects. This study aims to analyze the form of legal protection for debtors in the PKPU process, identify factors that influence the effectiveness of such protection, and examine the legal implications of Decision Number 8/Pdt.Sus-PKPU/2025/PN Niaga Medan on business continuity and debtor good faith. The research method used is normative legal research with a statutory approach and a case approach. The data used are primary, secondary, and tertiary legal materials that are analyzed qualitatively. The results of the study indicate that legal protection for debtors in PKPU has been normatively regulated through the provision of a suspension period, the opportunity for debt restructuring, and protection from creditor execution actions. However, its effectiveness is influenced by several key factors, namely the quality of regulations, the integrity of law enforcement officials, the debtor's good faith, the dominance of creditor interests, and the debtor's economic condition. In the context of Decision Number 8/Pdt.Sus-PKPU/2025/PN Niaga Medan, it was found that the decision has multidimensional legal implications: it provides room for business rescue for debtors, but also requires evidence of real good faith in fulfilling debt repayment obligations.